1998
DOI: 10.1086/311164
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the [TSUP]3[/TSUP][ITAL]P[/ITAL][TINF]2[/TINF] → [TSUP]3[/TSUP][ITAL]P[/ITAL][TINF]1[/TINF] Submillimeter Transition of [TSUP]13[/TSUP]C [CSC]i[/CSC] in the Interstellar Medium: Implication for Chemical Fractionation

Abstract: We report the first detection of the submm emission from the 13 C isotope of atomic carbon in the ISM. The F = 5 / 2 − 3 / 2 component of the 3 P 2 − 3 P 1 transition was observed with the CSO in a region ∼ 4 ′ S of Orion IRc2, near the western end of the Orion Bar. The 12 C to 13 C isotopic abundance ratio is 58 ± 12 corrected for opacity of the 12 C I line and the fractional intensity of the 13 C I hyperfine component (60%). This is in agreement with the value for the equivalent ratio in C + . In comparison,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
52
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 17 publications
7
52
2
Order By: Relevance
“…As the regions observed are photon dominated, we argue that the apparent enhancement in the abundance of 13 C towards G 333.0-0.4 may be due to strong isotope-selective photodissociation of 13 CO, outweighing the effects of chemical isotopic fractionation as suggested by models of PDRs. Towards NGC 6334 A and G 351.6-1.3 these effects appear to be balanced, similar to the situation for the Orion Bar region observed by Keene et al (1998). …”
supporting
confidence: 80%
“…As the regions observed are photon dominated, we argue that the apparent enhancement in the abundance of 13 C towards G 333.0-0.4 may be due to strong isotope-selective photodissociation of 13 CO, outweighing the effects of chemical isotopic fractionation as suggested by models of PDRs. Towards NGC 6334 A and G 351.6-1.3 these effects appear to be balanced, similar to the situation for the Orion Bar region observed by Keene et al (1998). …”
supporting
confidence: 80%
“…The recent observation of the 13 CI 3 P 2 → 3 P 1 transition in the Orion Bar indicates a high column of 13 C there, which suggests little chemical fractionation of 13 C into 13 CO, possibly due to isotope-selective photodissociation of 13 CO in the PDR (Keene, Schilke, et al, 1998).…”
Section: The Origin Of [Ci] Emissionmentioning
confidence: 98%
“…CO shielding functions have been tabulated by van and by Lee et al (1996). For low ratios of G 0 /n, the effects of CO self-shielding can lead to isotopic fractionation effects at the borders of clouds, where the rarer CO isotopes are preferentially photodissociated (Bally and Langer, 1982;Chu and Watson, 1983;Glassgold et al, 1985;Viala et al, 1988;Gredel et al, 1994;Warin et al, 1996;Keene, Schilke, et al 1998). However, the location of the C ϩ /C/CO transition in bright PDRs is largely governed by dust extinction.…”
Section: Pdr Chemical Network a Oxygen And Carbonmentioning
confidence: 99%
“…Following Wakelam & Herbst (2008) we assume a standard elemental abundance of 13 C/ 12 C of 67 in the solar neighbourhood. Observing 13 [C i] and 13 C 18 O in the Orion Bar Keene et al (1998) found little evidence for chemical fractionation. Their observations showed a slight enhancement of C 18 O/ 13 C 18 O = 75 and no enhancement of [ 13 Ci]/ [Ci] relative to the standard elemental abundance while the chemical models predicted the opposite.…”
Section: Introductionmentioning
confidence: 94%
“…Carbon fractionation in molecular and diffuse clouds has been discussed systematically by Keene et al (1998) and Liszt (2007). Following Wakelam & Herbst (2008) we assume a standard elemental abundance of 13 C/ 12 C of 67 in the solar neighbourhood.…”
Section: Introductionmentioning
confidence: 99%